História e cultura indígenas nas licenciaturas em Ciências Biológicas de universidades públicas do estado de São Paulo: presenças e ausências - Heloísa Beltrami Chain; Marcela de Moraes Agudo (Revista Crítica de Ciências Sociais)
This work investigates the inclusion of indigenous culture in the initial training of Science and Biology teachers, since its teaching is stipulated by law in Brazilian Basic Education, in a mandatory and transversal manner. Pedagogical Political Projects (PPP), extension projects and course completion work from the twenty campuses of higher education institutions that offer the Biological Sciences course were analyzed in São Paulo State, Brazil. The presence of indigenous culture was verified in contexts that value ethnic-racial diversity and the articulation of indigenous and scientific knowledge. Although the PPPs are the curricular space in which this discussion is most advanced in universities, there is still evidence of the invisibility of the topic, marked by the absence of mentions, especially in certain fields of research and extension.